Strategi Penghijauan Lingkungan Melalui Penanaman Bibit Pohon Produktif di RT 03 RW 01 Pematang Gubernur - Wahyudi, Wahyudi; Permata, Puja Dwi; Amanah, Nurrulita; Ramadano, Ebben Sah; AH, Alkausar; Febrianto, Yogi; Prasetya, Andwini; Susena, Karona Cahya; Yulianti, Liza (Jurnal Dehasen Untuk Negeri, 2026)
Environmental issues in RT 03 RW 01 Pematang Gubernur include the presence of arid land in water catchment areas, which increases the risk of soil erosion. The Thematic Community Service (KKN-T) Program of Group 30 from Dehasen University Bengkulu aims to address these issues through a strategic reforestation initiative. The methods employed include participatory observation and mutual cooperation in tree planting with the local residents. The activity was conducted on January 11, 2026, involving the planting of productive fruit tree seedlings, including durian, matoa, Jamaican guava, and rambutan. The results show an increase in vegetation coverage, which serves as natural shade and a soil erosion inhibitor. Beyond the ecological benefits, the selection of Multipurpose Tree Species (MPTS) provides long-term economic and nutritional value for the community. In conclusion, integrating reforestation programs with productive plants effectively enhances community participation and environmental sustainability.